Influence of the Probiotics of Lactobifadol on the Exchange Processes, Literal Microbiocenosis, Productive Indicators of Goslings - Ayrat Khabirov (Journal of Global Pharma Technology, 2016)
Inclusion of the probiotic supplement based on lactobacilli L.acidophilus and bifidobacterium B. Adolescentis to the diet of young poultry (goslings) at a rate of 0.2 g per 1 kg of body weight weekly, with subsequent weekly intervals, throughout the growing period provided: an increase in live goslings weights at 62 days of age by 3.7% compared with the intact group. The introduction of probiotic Lactobifadol to the body of goslings had a stimulating effect on protein and carbohydrate metabolism. The average total protein content from 20 days to 62 days in the control group increased by 12.6%, compared to the control group. In the blood serum of goslings, the average glucose content from 20-day to 62-day in the experimental group increased by 4% compared with intact birds. The average content of calcium and phosphorus in the blood serum of goslings of the experimental group from 20 days to 62 days of age was 14.8% less than in the control group of goslings. In the intestinal microbiocenosis, changes have occurred in the direction of an increase in the number of lactobacilli and bifidobacteria, with a significant decrease in the representation of E. coli. The use of Lactobifadol allowed to obtain a higher yield of gutted carcasses from goslings, to increase the mass of gutted carcasses by 6.64%. The use of Lactobifadol in growing of goslings allowed to receive an additional income of 23 rubles per 1 head.Keywords: Probiotic Lactobifadol, Goslings, Live weight, Daily average growth, Morphological blood parameters, Serum biochemical parameters, Microflora, Lactobacilli, Bifidobacteria, E. coli, Meat quality, Eviscerated carcass yield, Economic efficiency.